1998
DOI: 10.1021/es980217h
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Description of Aquatic Colloidal Interactions:  The Three-colloidal Component Approach

Abstract: This paper describes several possible interactions among the different types of organic and inorganic aquatic colloids, based on our present knowledge of their size, electric charge, and conformation. The physicochemical properties of the different groups of colloids are described. Emphasis is placed on the various types of organic components, including fulvic compounds. Subsequently, the role of each colloid class is discussed with respect to homoaggregation (aggregation within a given colloid class) and hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
401
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 517 publications
(423 citation statements)
references
References 58 publications
21
401
1
Order By: Relevance
“…Humic substances (HS) represent an active and important fraction of natural organic matter (NOM), and they play important roles in the fate and transport of pollutants (Aiken, 1985;Buffle et al, 1998;Zheng et al, 2008). HS can be categorized into three groups: fulvic acids (FAs), which are the major component and the smallest structures of HS, and are soluble at any pH; HA, which represents bigger structures that are insoluble at pH b 2; and humin, which is insoluble at any pH (Jones and Bryan, 1998;Piccolo, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Humic substances (HS) represent an active and important fraction of natural organic matter (NOM), and they play important roles in the fate and transport of pollutants (Aiken, 1985;Buffle et al, 1998;Zheng et al, 2008). HS can be categorized into three groups: fulvic acids (FAs), which are the major component and the smallest structures of HS, and are soluble at any pH; HA, which represents bigger structures that are insoluble at pH b 2; and humin, which is insoluble at any pH (Jones and Bryan, 1998;Piccolo, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of decreasing the coagulation rates of the inorganic particles as has been observed for the HS (Tipping and Higgins 1982;Amal et al 1992)(see Chpater 5), it has been suggested that the rigid biopolymers may increase the coagulation rate of inorganic particles Buffle et al 1998).…”
Section: Introductionmentioning
confidence: 89%
“…Inorganic particles are generally electrically charged due to the isomorphic substitution of ions in the bulk solid phase, or to the reactions of surface functional groups with dissolved ions in the aqueous phase (Sposito 1993). Apart from the iron oxyhydroxydes which are neutral or positively charged in the circumneutral pH range, the major inorganic colloids are generally negatively charged in water due to their low zero point of charge (Table 1; (Lerman 1979;Buffle et al 1998)). It is therefore reasonable to represent the submicron inorganic colloids as compact, often negatively charged particles that cover the whole colloidal size range.…”
Section: Inorganic Colloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace metals and organic pollutants are mainly adsorbed at the surface of mineral particles like silicates, alumino-silicates or iron oxyhydroxides [3,4] owing to their high specific surface area, diffusivity and reactivity. In these systems algal and bacterial exudates composed of polysaccharide chains promote the flocculation of these mineral particles and the subsequent removal of pollutants.…”
Section: Introductionmentioning
confidence: 99%